2020
DOI: 10.1007/978-3-030-50841-8_13
|View full text |Cite
|
Sign up to set email alerts
|

Transcending the Loading Dock Paradigm—Rethinking Science-Practice Transfer and Implementation in Sustainable Land Management

Abstract: Modern science is increasingly called on to produce societally relevant and usable knowledge to tackle global challenges. Academics respond by conducting research projects that transcend the boundaries of single disciplines and institutions by actively engaging with non-academic actors. Such institutional arrangements open up entirely new perspectives for science communication and the problem-solving of real-world issues. However, they also call for elaborate management tasks and demand learning processes on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Although the literature presents ways to engage in effective KE, there are fewer empirical examples of how this can be done and what factors enable KE for impactful environmental and natural resource management Reed et al, 2018;Walsh et al, 2019). As such, practitioners often perform KE based on what has worked in the past, emphasizing the need to identify the enabling conditions for practicing effective KE (Reed et al, 2014;Matzek et al, 2014;LSE 2019), A recurrent theme for improving KE at the interface of environmental science and policy is transitioning away from linear modes of communication and engagement i.e., generating and exchanging knowledge that does not specifically address a target audience and is not generally available or accessible to all knowledge users (Cash et al, 2006;Beier et al, 2017;Rogga, 2021) towards more interactive multi-directional modes of KE i.e., one that facilitates collaborative communication between knowledge producers and users and engages knowledge users in all aspects of the research process (Cook et al, 2013;Stewart et al, 2014;Bautista et al, 2016;Cvitanovic et al, 2021). A range of approaches have been identified that enable more interactive and collaborative KE and includes the use of science-policy intermediaries such as boundary spanners and boundary organizations (Bednarek et al, 2018), building relationships and trust between knowledge producers and users to maintain ongoing communication to produce useable science (Fazey et al, 2014;Cook et al, 2020;Cvitanovic et al, 2021), improving organizational structures such as embedding knowledge producers within research organizations to conduct long-term research (Roux et al, 2019;Walsh et al, 2019), acquiring sufficient resources (such as funding, time, and staff) to complete projects (Meadow et al, 2015), and improving organizational culture to support the use of scientific evidence (Walsh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although the literature presents ways to engage in effective KE, there are fewer empirical examples of how this can be done and what factors enable KE for impactful environmental and natural resource management Reed et al, 2018;Walsh et al, 2019). As such, practitioners often perform KE based on what has worked in the past, emphasizing the need to identify the enabling conditions for practicing effective KE (Reed et al, 2014;Matzek et al, 2014;LSE 2019), A recurrent theme for improving KE at the interface of environmental science and policy is transitioning away from linear modes of communication and engagement i.e., generating and exchanging knowledge that does not specifically address a target audience and is not generally available or accessible to all knowledge users (Cash et al, 2006;Beier et al, 2017;Rogga, 2021) towards more interactive multi-directional modes of KE i.e., one that facilitates collaborative communication between knowledge producers and users and engages knowledge users in all aspects of the research process (Cook et al, 2013;Stewart et al, 2014;Bautista et al, 2016;Cvitanovic et al, 2021). A range of approaches have been identified that enable more interactive and collaborative KE and includes the use of science-policy intermediaries such as boundary spanners and boundary organizations (Bednarek et al, 2018), building relationships and trust between knowledge producers and users to maintain ongoing communication to produce useable science (Fazey et al, 2014;Cook et al, 2020;Cvitanovic et al, 2021), improving organizational structures such as embedding knowledge producers within research organizations to conduct long-term research (Roux et al, 2019;Walsh et al, 2019), acquiring sufficient resources (such as funding, time, and staff) to complete projects (Meadow et al, 2015), and improving organizational culture to support the use of scientific evidence (Walsh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%